Fatigue resistance of polymeric restorative materials: effect of supporting substrate - Facenda, Júlia Cadorim; Borba, Márcia; Benetti, Paula; Borges, Alexandre Luiz Souto [UNESP]; Dutra, Mauro Dal Zot; Corazza, Pedro Henrique (My University, 2023)
The objective of this study was to investigate the effect of mismatch between the elastic properties of substrate and restorative material on the fatigue resistance and stress distribution of multilayer structures. The tested hypotheses were that (1) both an indirect composite resin (IR) and a polymer-infiltrated ceramic network (PICN) would show a higher survival rate after cyclic loading when cemented to a substrate with a high elastic modulus (E); and (2) PICN structures would have higher survival rates than IR structures regardless of the supporting substrate. Blocks of PICN and IR were cut to obtain 1.0-mm-thick sections, which were cemented to substrates with different E values: c, core resin cement (low E); r, composite resin (intermediate E); and m, metal (nickel-chromium alloy; high E). The resulting 6 groups of specimens (n = 20 per group) were subjected to a cyclic fatigue test (106 cycles). Stress distribution was verified using finite element analysis, and the risk of failure was estimated. Fatigue data were analyzed using Kaplan-Meier and Holm-Šidák tests. The χ2 test was used to evaluate the type of crack. The groups IRc, IRr, and PICNm had the highest survival rates after cyclic loading and were statistically similar to each other. Their survival rates were significantly greater than those of the IRm, PICNr, and PICNc groups (P < 0.001), which were all significantly different from each other (P < 0.001). There was a significant relationship between the experimental group and type of crack (P < 0.001). Specimens cemented to core resin cement and composite resin substrates showed predominantly radial cracks, while those cemented to nickel-chromium alloy had predominantly cone cracks. The risk of failure values revealed that PICN was more sensitive to the type of substrate than IR. PICN has greater fatigue-resistant behavior when cemented to a substrate with a high E value, while IR has superior performance when substrates with lower and intermediate E values are used.
Keywords: composite resin; elastic modulus; fatigue; finite element analysis; flexural strength; polymer-infiltrated ceramic-network material